THE INFLUENCE OF SELF-CONCEPT AND SELF-CONTROL IN REDUCING AGGRESSIVE BEHAVIOR AMONG STUDENTS OF ISLAMIC BOARDING SCHOOLS IN BEKASI - Bilqisthi Zhahiriyah (Adisam Publisher, 2025)
Aggressiveness is motivated by internal and external factors, one of the internal factors is low self-concept and self-control. Student who have a positive self-concept will carry out positive actions as expected, otherwise a negative self-concept will make teenagers tend to violate the rules or norms of society and eventually get involved in juvenile delinquency. Basically a failure of self-control can contribute to most aggressive actions that involve violence. This study aims to determine how the influence of self-concept and self-control in reducing aggressive behavior in Islamic boarding school students in Bekasi. This research is a descriptive research with the type of correlational research, the sampling technique used is purposive sampling, with a population of 420 students with a total sample of 99 people. The instrument used in this study used a questionnaire in the form of a scale which refers to the self- concept scale measuring instrument, namely the Tennessee self-concept scale (TSCS) compiled by Fitts (1971) a scale adapted from Averill (1973) Aggression Questionnaire Buss and Perry (1992). The results of the study showed that there was no effect between self-concept and self-control in reducing the aggressive behavior of students at the boarding school. It was found that the significance coefficient on the self-concept variable was 0.146 with β = 0.150 (or 15.0%). Meanwhile, it is also known that the significance coefficient on the self-control variable is 0.708 with β = (-0.067 or -67%). This shows that the two variables together have no effect on the aggressiveness variable.